2006
DOI: 10.1097/01.iop.0000214531.58587.57
|View full text |Cite
|
Sign up to set email alerts
|

Amaurosis After Lower Eyelid Laser Blepharoplasty

Abstract: The transconjunctival CO(2) laser approach to lower eyelid blepharoplasty was used to treat a 66-year-old man presenting with bilateral lower eyelid herniated fat without excess skin. Early postoperative examination revealed left eye blindness. This report presents clinical circumstances of this rare complication and further discusses the most likely causative factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Vision loss may ensue from microvascular compression that leads to ischemic optic neuropathy. [22][23][24][25] It has also been postulated that a tense orbit may exceed the mean arterial pressure of the ophthalmic artery or central retinal artery resulting in central retinal artery occlusion. [26][27][28][29][30][31][32] With prompt treatment vision loss can be reversible after retrobulbar hemorrhage.…”
Section: Deep Orbital Hemorrhage and Severe Vision Lossmentioning
confidence: 99%
“…Vision loss may ensue from microvascular compression that leads to ischemic optic neuropathy. [22][23][24][25] It has also been postulated that a tense orbit may exceed the mean arterial pressure of the ophthalmic artery or central retinal artery resulting in central retinal artery occlusion. [26][27][28][29][30][31][32] With prompt treatment vision loss can be reversible after retrobulbar hemorrhage.…”
Section: Deep Orbital Hemorrhage and Severe Vision Lossmentioning
confidence: 99%
“…Retinal changes are observed mainly at early stages with the rise of retrobulbar hemorrhage after the blepharoplasty, followed by the application of local anesthetics containing epinephrine, vasospasm, inflammation, and systemic hypotension, respectively [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Çalık et al reported that iatrogenic cystoid macular edema and papillitis decreased spontaneously at week 5 after surgery [33]. Transient visual loss after transconjunctival lower lid blepharoplasty was reported, which was considered to be associated with vascular spasm in retina or optic nerve circulation [31]. Macular thickness alterations are also observed after the strabismus surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Some cases may require a second surgery correction because of insufficient removal of fat bags. Other complications include infection, scleral show, conjunctivitis, corneal ulcer, diplopia, amaurosis, and damage of both the inferior oblique muscle and the orbicularis oculi muscle [11] [12]. Table 2 shows the complications reported in patients who underwent the transconjunctival approach versus the transcutaneous approach.…”
Section: Resultsmentioning
confidence: 99%